ADMINISTRATION EFFICACY OF TINCTURE FROM LEMNA MINOR FROND FOR LIPID PROFILE CORRECTION IN EXPERIMENTAL HYPOTHYROIDISM - Kononenko, A.G.; Kravchenko, V.M. (World of Medicine and Biology, 2016)
The experimental study of influence of 30% tincture from Lemna minor frond on lipid metabolism in rats with hypothyroid state carried out. Experimental hypothyroidism in rats induced the introduction of a 1% solution of sodium perchlorate instead of drinking water for 20 days. After 20 days the experimental animals with hypothyroidism administered 30% tincture from Lemna minor frond at a dose of 1 ml/100 g body weight, reference drug Iodomarin at a dose of 12 µg iodine/kg and 30% ethanol solution as a negative control group. Results of study showed significant corrective action of 30% tincture from Lemna minor frond on synthetic thyroid function and lipid profile of blood serum in hypothyroid state, which manifested in the normalization of thyroid hormones level, decreasing of total lipids, total cholesterol, LDL and triglycerides. Found that the introduction of a 30% ethanol solution did not lead to positive changes in the lipid spectrum. Thus, 30% tincture from Lemna minor frond can be recommended as a regulator of thyroid gland hypofunction and lipid profile and are promising for further study of its effectiveness.